'n Diagnose van die personeelbestuurstelsel van 'n boerderyonderneming met behulp van die personeelbestuursoudittegniek : 'n Likert-tipe ontleding - Coetzee, Leon (University of the Free State, 1989)
The main problem in the study is that the efficiency and effectiveness of personnel management on farms in the RSA is not satisfactory and even in the best firms the management practices and policies of the managers are very inadequate in comparison with the staff's expectations. An important reason for this is that the role of the work attitudes of the workers is not taken into sufficient consideration by the farmers. The case study method was used to collect the personnel audit data of a farmer and 47 farm workers. The personnel audit form is a Likert type questionnaire consisting of 19 questions that measure the experiences and expectations of the staff in respect of motivation, communication, human relationships, control, and job performance. A considerable degree of confirmation was found for the hypotheses posed: 1. The questions in the adjusted personnel audit were compiled, grouped and presented in such a way by means of the block and peg apparatus that literate and semi-literate farm workers were able to register their perceptions of their work environment as far as their experiences, as well as expectations were concerned. 2. The work experiences of the staff differ to such an extent from their work expectations in respect of the leadership, motivation, communation, human relationships and personnel performance system in the firm that their productivity and job satisfaction would improve considerably. In general the productivity and job satisfaction of the workers could improve - (a) if a more participative leadership system were implemented; (b) if the hygiene factors were improved and the motivating factors were implemented at the same time; (c) if a formal communication system were implemented; (d) if human relationships were more supportive; and (e) if a continuous in-service training programme were implemented to satisfy the great need for training which the workers experience. 3. The work experiences of the staff correspond, to a large extent, to their work expectations in respect of the personnel control system in the firm. 4. Factors such as the hierarchical post level of the worker, or type of work, age of the worker, ethnic group, period of service, and degree of westernization as measured by the years of experience on farms in the RSA can explain the differences between the work experiences and work expectations of the workers to a small extent only. 5. The work experiences and work expectations of the staff in respect of leadership, communication, human relationships, and control correspond to a large extent to the farmer's predictions thereof, and therefore these practices are effective. 6. The work experiences and expectations of the staff in respect of motivation and performance do not correspond to a great extent to the farmer's predictions thereof, and consequently the efficiency and effectiveness of the farmer's motivation and productivity strategy leaves considerable room for improvement. As far as the motivation strategy is concerned, the farmer does not realize to an adequate extent that Herzberg's motivators and hygiene factors can be used more effectively. In respect of the productivity strategy, the farmer is not aware to an adequate extent that the workers generally experience a great need for training and at the same time expect to be trained. 7. In future the farmer could identify and regulate the weak and strong points in the personnel management system by using the diagnostic instrument system to measure the work attitudes of the staff. The most important recommendation is that a personnel management development strategy be designed in order to improve diagnosed weak points in the personnel management system and to develop the strong points further.
Dissertation (M.Sc.Agric. (Agricultural Economics))--University of the Free State, 1989
Keywords: Human resource management; Farms -- personnel management; Farm management -- South Africa; Agricultural administration -- South Africa